Does geographic context influence employability‐motivated volunteering? The role of area‐level material insecurity and urbanicity. (22nd March 2015) - Chum, Antony; Carpenter, Sara; Farrell, Eddie; Mook, Laurie; Handy, Femida; Schugurensky, Daniel; Quarter, Jack
<x xml:space="preserve">Abstract</x> There is a growing public discourse that volunteering increases the likelihood of finding a better job because it improves social and human capital. While previous studies have largely treated volunteers' motivations as individualistically determined, contextual determinants of volunteers' motivations are relatively neglected. The purpose of this study is to understand the individual and contextual characteristics in which individuals are more likely to volunteer as a means of improving their employability. Using a random sample of 768 volunteers across Canada, we estimate the independent effects of a) municipal‐level material insecurity, b) urbanicity, and c) individual characteristics on the odds of "volunteering to improve employability." Our findings show that living in municipalities with high economic insecurity and in urban settings independently increases the odds of volunteering to improve employability. Our study points to evidence of model misspecification, by omission of unobserved geographical covariates, in previous studies of volunteers' motivations.